The Implementation of Sepatin Village Community Empowerment Program as the Blue Carbon Initiative Project of the Mahakam Delta - Apriani, Fajar; Selamet, Sutrimo (Department of Public Administration, Muhammadiyah University of Makassar, 2025)
The Community Empowerment Program in Sepatin Village is part of the Blue Carbon Initiative Project of the Mahakam Delta. Sepatin Village is situated in the coastal area of Kutai Kartanegara Regency, East Kalimantan. This research aims to analyze the implementation of the Sepatin Village Community Empowerment Program within the context of mangrove forest rehabilitation and restoration in Sepatin Village, a coastal village located in the Mahakam Delta. Through qualitative approach and case studies, the research results show that the Sepatin Village Community Empowerment Program has been implemented well with involving the community in mangrove rehabilitation and restoration activities, training in hydroponic plant cultivation, installing solar-powered street lights, and providing rainwater harvesting facilities. For developing this Community Empowerment Program, there is potential for fishermen’s catch, which is currently still unutilized, to be processed into value-added products. So, for the sustainability of efforts to improve the welfare of the Sepatin Village community, further assistance efforts are needed from Mulawarman University academics who can also act as distributors of these processed products.